2000
DOI: 10.1139/a00-008
|View full text |Cite
|
Sign up to set email alerts
|

Stable lead isotope characteristics of lead ore deposits of environmental significance

Abstract: Stable Pb isotopes are increasingly used in environmental science as tracers of natural and anthropogenic Pb sources. This review provides a summary of the recent geological literature concerning Pb isotopes in global Pb ore deposits. The isotopic characteristics of 151 Pb deposits, including 78 20th-century producing mines, have been summarized using the 204Pb-based ratios common to geological science and the 206Pb- and 207Pb-based ratios (i.e., excluding 204Pb) more often employed in environmental studies. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(89 citation statements)
references
References 69 publications
3
82
0
1
Order By: Relevance
“…Phenocrysts from the young SSI volcanic material should Leat et al [2004], and the Southern Thule Group from Leat et al [2003]. Grey fields are modern lead data from Sangster et al [2000]. Dotted line marks the two-step common lead age model of Stacey and Kramers [1975].…”
Section: Sources Of Clear Mineralsmentioning
confidence: 99%
“…Phenocrysts from the young SSI volcanic material should Leat et al [2004], and the Southern Thule Group from Leat et al [2003]. Grey fields are modern lead data from Sangster et al [2000]. Dotted line marks the two-step common lead age model of Stacey and Kramers [1975].…”
Section: Sources Of Clear Mineralsmentioning
confidence: 99%
“…206 Pb/ 204 Pb,207 Pb/ 206 Pb,87 Sr/ 86 Sr) can provide clearer evidence for anthropogenic input compared to concentrations data alone, as the different anthropogenic sources, whether point-source or of regional scale, commonly show distinct characteristic isotope compositions compared to those found in natural sediments (e.g., Hamelin et al, 1990;Monna et al, 1997). The signatures of "heavy" isotope may ultimately be related to the isotope geochemistry of the ore deposit from which the industrial element was produced (Sangster et al, 2000). In the case of Pb air pollution, impact studies were supported, since the 1980s (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The data in this study do not indicate a concomitant rise in Fe, Mn or Ti with Pb, Ca and associated elements with data grouped over the range 0-24 m to > 200 m (Supplementary materials Table SM-4) reducing the likelihood of contamination related to brake dust from vehicles being a dominant factor. Mao et al (2014) demonstrated that London soils have a relatively narrow range of 206 Pb/ 207 Pb falling on a mixing line between geogenic (UK coal and UK Pb ore; Shepherd et al, 2016) and UK leaded petrol (1.06-1.09 Shepherd et al, 2016;Chenery et al, 2012;Sangster et al, 2000) suggesting multiple sources of Pb contamination including petrol, paint, water pipes, coal ash. Whereas Total Pb does not correlate with 206 Pb/ 207 Pb, it is the primary determinant of isotopically exchangeable Pb (Mao et al, 2014) as it is for bioaccessible Pb .…”
Section: Warmentioning
confidence: 99%